Հայոց ցեղասպանութեան իմաստաւորման հարցը - Սարգսեան, Արմէն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена вопросу осмысления Геноцида армян 1915 года. Несмотря на то, что на эту тему можно найти много научных исследований, императив осмысления первого геноцида XX века все еще остается весьма актуальным. Автор статьи в контексте феномена ресентиментa показывает, что в условиях современных реалий понимание мести и долга мести за геноцид должно быть переосмыслено, поскольку «торможение» ответного удара может еще сильнее развить комплекс жертвы. Мы должны преодолеть этот комплекс и путем духовного обновления создать свое будущее. Автор обосновывает, что современный дискурс прощения турок или Турции за Геноцид армян является искусственным, манипулятивным, поскольку реально простить может только тот, кто имеет потенциал непрощения, тот, кто добивается безальтернативного покаяния виновного. The article is dedicated to the issue of comprehending the Armenian Genocide of 1915. Despite the fact that there is a lot of scientific research regarding the Armenian Genocide, the imperative of understanding the first genocide of the 20th century is still very relevant. The author of the article, in the context of the phenomenon of sentiment, shows that in modern realities, the understanding of revenge and the duty of revenge for genocide should be rethought, since the “inhibition” of the retaliatory strike can further develop the victim’s complex. We should overcome this complex and create our future through spiritual revival. The author substantiates that the modern discourse of the forgiveness of the Turks or Turkey for organizing the Armenian Genocide is artificial, manipulative, since only one who has the potential for unforgivingness, one who seeks no alternative repentance of the culprit can really forgive.